First experience in Switzerland in Phe508del homozygous cystic fibrosis patients with end-stage pulmonary disease enrolled in a lumacaftor-ivacaftor therapy trial – preliminary results (Swiss Medical Weekly, 2018)
AIMS OF THE STUDY Cystic fibrosis is the most common genetic disorder in Caucasians. The combination of the cystic fibrosis transmembrane conductance regulator (CFTR) corrector lumacaftor / potentiator ivacaftor (LUM/IVA) has been shown to increase forced expiratory volume in 1 second (FEV1) moderately, but predominantly reduce acute exacerbation rate (AER) in Phe508del homozygous cystic fibrosis patients; however, patients with FEV1